PELATIHAN PENULISAN BUKU UNTUK GURU SD DAN SMP SATAP CONGGORO - GH, Muliana; Adnan, Adnan; Arsal, Andi Faridah; Suryani, Andi Irma; Sadriani, Andi (Paramacitra Jurnal Pengabdian Masyarakat, 2025)
This activity aims to improve book writing skills among teachers at SD and SMP Satap Conggoro, Gowa Regency. The ability to write books is an essential aspect of teacher professionalism, particularly in supporting the quality of education. Through this training, teachers are expected to overcome challenges in writing books and academic papers. The training methods include lectures, discussions, and hands-on practice. The results of the activity showed an increase in teachers' understanding of the importance of literacy in education, as well as book writing skills that can be applied to enhance teacher professionalism.